I am not your perfect Mexican daughter [book club bag] - Sánchez, Erika L. (Alfred A. Knopf Books for Young Readers, 2017)
Perfect Mexican daughters do not go away to college. And they do not move out of their parents' house after high school graduation. Perfect Mexican daughters never abandon their family. But Julia is not your perfect Mexican daughter. That was Olga's role. Then a tragic accident on the busiest street in Chicago leaves Olga dead and Julia left behind to reassemble the shattered pieces of her family. And no one seems to acknowledge that Julia is broken, too. Instead, her mother seems to channel her grief into pointing out every possible way Julia has failed.